Enfranchisement, political participation and political competition: evidence from colonial India - Cassan, Guilhem,Lakshmi Iyer,Ali Mirza, Rinchan (IZA - Institute of Labor Economics, 2020)
We examine how political participation and political competition are shaped by two class-based extensions of the franchise in 20th-century India. Creating a new dataset of district level political outcomes between 1921 and 1957, we find that the partial franchise extension of 1935 resulted in significantly lower incumbency advantage, while the institution of universal adult suffrage in 1950 resulted in increased candidacy. Both these franchise extensions resulted in decreased voter turnout rates, suggesting that newly enfranchised voters are less engaged in the political process.
10419/223918
Keywords: Graue Literatur; democratization; colonial rule; India; franchise extension; political participation; political competition